Viscosity of binary refrigerant mixtures of R32 + R1234yf and R32 + R1243zf. (August 2021) - Yang, Xiaoxian; Liu, Hangtao; Chen, Shi Hai; Kim, Dongchan; Yang, Fufang; Arami-Niya, Arash; Duan, Yuanyuan
Highlights: Viscosity of R32+R1234yf and R32+R1243zf were measured in liquid and gas phases. Relative combined uncertainties ( k = 2) in viscosity are generally from 3.2 to 5.0 %. Parameters of the RES-CPA model for pure R1243zf and R32 + R1243zf were fitted. Relative deviation of measured viscosities from the RES-CPA model is within 10%. Abstract: Viscosity measurements of six binary mixtures of R32+R1234yf and R32+R1243zf at different compositions were conducted in the homogenous liquid and gas phases with a vibrating-wire viscometer in the temperature range from (254 to 383) K and pressures from (1 to 8) MPa. The measurement system was verified with the measurements of pure carbon dioxide and R32 in homogenous liquid and gas phases. The relative combined expanded uncertainties ( k = 2) in the experimental viscosity of the mixtures are generally from 3.2% to 5.0%. The measured viscosities agree with the calculations of the extended corresponding state model implemented in the software package REFPROP 10.0 within 10% and mainly within 5%. The parameters of the residual entropy scaling model incorporating cubic-plus-association equation of state (RES-CPA model) for the viscosity of pure R1243zf and binary R32 + R1243zf mixture were determined. The relative deviation of the measured viscosities from values calculated with the RES-CPA model is mainly within 6% in the liquid phase and 10% in the gas phase. Graphical abstract: Image, graphical abstract